Analisis Faktor "Pemicu" Minat Melakukan Whistleblowing - Aida Nahar (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
This study aims to analyze the factors that trigger employee interest in whistleblowing. The population in this study were employees who worked in the OPD as a financial sub division and one financial staff member from all Regional Apparatus Organizations (OPD) in Jepara Regency using simple random sampling. The results showed that the factors that triggered employee interest in whistleblowing were employee attitudes, organizational commitment, personal costs and the seriousness level of employee fraud. The better the employee's attitude which is shown by agreeing to disclose the fraud, the greater the person's interest in taking whistleblowing. The greater the employee's commitment to an organization, the greater the employee's interest in uncovering the fraud or in whistleblowing. The higher the risk faced by employees as indicated by the high personal cost to reveal the occurrence of fraud, the lower the employee's interest in reporting fraud or the lower the interest in whistleblowing. In addition, the higher the seriousness level in eradicating fraud, the higher the employee's interest in exposing the fraud to the authorities by becoming a whistle-blower, which also means that employees' interest in taking whistleblowing action will be higher.